Selective mobility, segregation and neighbourhood effects - Boschman, Sanne (A+BE | Architecture and the Built Environment, 2015)
Introduction The residential neighbourhood is thought to affect residents because of presumed neighbourhood effects; the independent effects of a neighbourhood’s characteristics on the life chances of its residents. An enormous body of research has tried to measure neighbourhood effects, however, there are no clear conclusions on how much, if any, effect the neighbourhood has on its residents. There is non-random selection of people into neighbourhoods which causes a bias in the modelling of neighbourhood effects. Any correlation found between neighbourhood characteristics and individual outcomes might be explained by selection bias and can therefore not prove the existence of a causal neighbourhood effect. The question is; do poor neighbourhoods make people poor, or do poor people live in unattractive neighbourhoods because they cannot afford to live elsewhere (Cheshire, 2007). Therefore, insight in selection is important to gain more insight in neighbourhood effects (Van Ham and Manley, 2012). For neighbourhood effects research it is important to study selective mobility and neighbourhood choice and to combine neighbourhood effects research with neighbourhood selection research (Doff, 2010a; Van Ham and Manley, 2012; Van Ham et al., 2012; Galster, 2003; Hedman, 2011). The aim of this thesis therefore is to gain more insight in both the causes and the consequences of segregation and thus to study both individual residential mobility and neighbourhood selection and neighbourhood effects. Besides the neighbourhood effects literature, also the segregation literature will benefit from better insights in selective residential mobility because selective residential mobility is one of the main driving forces of segregation. There are two main research questions for this thesis. Firstly, I try to give insight in selective mobility and neighbourhood choice and thus to study where, when and why which people move. What is the effect of personal characteristics, neighbourhood characteristics and macro level housing market developments on individual neighbourhood satisfaction, moving wishes, moving behaviour and neighbourhood selection and on macro level selective mobility patterns and segregation? Secondly, I will test presumed neighbourhood effect mechanisms. Concentration areas of ethnic minorities are seen as undesirable, because their residents are thought to have less contact with the native majority which might hamper their integration and their life chances. It is, however, unclear to what extent social contact is affected by the residential neighbourhood. The second research question therefore asks whether ethnic minorities have less contact with the native majority if they live in minority concentration neighbourhoods. Segregation Segregation is defined as the population composition of neighbourhoods in relation to each other; that is, the concentration or underrepresentation of population groups in neighbourhoods compared to a city or national level average. Selective residential mobility is one of the main driving forces of segregation. Households move to a certain neighbourhood, either because they choose to live there, or because they are constrained in their choice options. Therefore segregation can be both voluntary and involuntary. This thesis focuses on selective residential mobility as cause of segregation, therefore it tries to understand why and where people move. According to residential mobility theory, personal characteristics determine residential preferences and if the residential situation is not in line with these preferences this will lead to dissatisfaction and a desire to move (Brown and Moore, 1970). Whether a dissatisfied household succeeds in moving to a dwelling and neighbourhood more in line with their preferences, depends on their personal resources and restrictions and macro level opportunities and constraints (Mulder and Hooimeijer, 1999). Successful households will move to a neighbourhood more in line with their preferences. There are, however, differences between households in which neighbourhoods are open to choice. Low income households will only be able to select neighbourhoods in which inexpensive dwellings are available. Similarly, households who depend on the social housing sector, or on the owner-occupied sector will only be able to select neighbourhoods where dwellings of this tenure are available. In addition, there are differences between households in which neighbourhood is (deemed) most attractive. People prefer to live among others who are similar to themselves and also facilities directed towards specific groups will make especially concentration neighbourhoods of the own ethnic or income group attractive. Besides residential preferences, also other factors will affect neighbourhood selection; population groups will differ in access to information on neighbourhood attractiveness or housing opportunities and discrimination, or fear of discrimination, can limit the opportunities of minority groups on the housing market. Neighbourhood effects It is typically assumed in European and American urban policy and academic research that spatial concentrations of low income households or ethnic minorities have negative effects on their inhabitants (Friedrichs et al., 2003). An enormous body of research has tried to measure neighbourhood effects; the independent effect of a neighbourhood on its residents when controlling for individual characteristics (see for a review Dietz, 2002; Ellen and Turner, 1997; Sharkey and Faber, 2014; Van Ham et al., 2012). The research attention for neighbourhood effects started with the seminal work of Wilson (1987). He argued that living in concentration areas of the jobless lowest class, isolated from role models, mainstream values and norms, and informal job networks and social contacts with employed, has a negative effect on your life chances. Neighbourhoods can affect their residents via a number of mechanisms (Ellen and Turner, 1997; Erbring and Young, 1979; Galster, 2012). Firstly, the geographicallocation determines job access and thereby labour market opportunities. Secondly, pollution, noise and disturbance affect health and (thereby) life chances via environmental mechanisms. In addition, neighbourhood stigmatisation can reduce life chances because others have prejudiced ideas and low expectations of the residents of stigmatised neighbourhoods. Also, the quality of institutions such as schools, museums, libraries and sport facilities will generally be lower in disadvantaged neighbourhoods, thereby reducing the life chances of residents. Finally, neighbourhood effects can transpire viasocial interactions with neighbours. Through collective socialisation and peer pressure people are thought to conform to local social norms (Jencks and Mayer, 1990). Positive role models and social network contacts with individuals with more social capital can help people advance in their work or educational career (Ellen and Turner, 1997). For ethnic minorities it can be important to have social interactions with the native majority to have the opportunity to learn the majority language, standards and values (Lazear, 1999) and to have bridging network ties that can provide access to valuable information not present within the own ethnic network (Buck, 2001). Many neighbourhood effect researchers believe that living in concentrated poverty has negative effects on individuals, and policymakers try to create mixed neighbourhoods to prevent these negative neighbourhood effects. However, although “it is perfectly plausible that poor people are made poorer by the characteristics of the neighbourhoods in which they live” (…) “a close examination of the best research available does not reveal any clear evidence to support it” (Cheshire, 2007: p. ix). Almost all neighbourhood effect studies struggle with selection bias (Cheshire, 2007). Any relation found between neighbourhood characteristics and individual outcomes might be a selection effect and therefore cannot prove the existence of a causal neighbourhood effect. Neighbourhood effects researchers have tried to reduce or eliminate selection bias. Firstly this is done by using quasi-experimental study designs, using households whose residential neighbourhood is determined by external factors (Sampson et al., 2002). Secondly, advanced statistical methods such as sibling studies, fixed effects studies, instrumental variables and propensity score matching are used to reduce selection bias or to control for selection (Harding, 2003). These advancements in methodology have improved our insight in selection bias and in neighbourhood effects, however, since there are no methods that can completely eliminate selection bias, there is still no clear evidence of causal neighbourhood effects. Generally, methods that apply more controls for selection bias find smaller neighbourhood effects. Instead of trying to eliminate selection bias, this thesis tries to provide insight in selection, in why and where which people move. In addition, this thesis tests presumed neighbourhood effect mechanisms. Social interactive mechanisms assume that neighbourhood effects transpire because the population composition of the residential neighbourhood affects with whom you interact (Ellen and Turner, 1997; Galster, 2012). Therefore I test whether the ethnic composition of the neighbourhood affects interethnic contact. Individual differences in determinants of residential satisfaction Residential satisfaction is a key variable in understanding individual residential mobility (Lu, 1999; Speare, 1974), as dissatisfaction leads to desires to move (Wolpert, 1965). Many researchers have studied the individual level and neighbourhood level determinants of residential satisfaction, however, very few have studied which neighbourhood characteristics are important to whom. People differ in which neighbourhood characteristics affect their residential satisfaction (Galster and Hesser, 1981). If certain neighbourhood characteristics lead to dissatisfaction and therefore to mobility desires for specific groups, this might lead to selective mobility and segregation. Therefore, in Chapter 2 I study individual differences in the determinants of residential satisfaction. I estimate ordered logit models explaining satisfaction on residents of urban areas within the Housing Research Netherlands 2012 survey. To test whether there are individual differences in the effects of neighbourhood characteristics on satisfaction I include interaction effects between individual characteristics and neighbourhood characteristics. These interaction effects test whether neighbourhood characteristics such as the neighbourhood ethnic composition, crime rates or dwelling values have similar effects on all individuals, or whether individual characteristics affect the size and direction of these effects. To my knowledge, previously only Greif (2015) and Parkes et al. (2002) have tested interaction effects between tenure and neighbourhood characteristics and there is no earlier research on ethnic or household differences in the determinants of neighbourhood satisfaction. Because there is almost no earlier research on individual differences in the determinants of satisfaction, I combine literature on residential satisfaction with literature on residential preferences, mobility desires and behaviour to create hypotheses about which neighbourhood characteristics are important to whom. In line with the literature, I find that the share of non-western minorities in the neighbourhood has a negative effect on neighbourhood satisfaction, an effect that is stronger for natives than for non-western minorities themselves. This can be explained by own group preferences; people are more satisfied in neighbourhoods with higher shares of their own ethnic group and when this is taken into account the differences between ethnic groups in the effect of the total neighbourhood share of non-western ethnic minorities on satisfaction disappear. Satisfaction is found to be more dependent on neighbourhood characteristics for owner-occupiers than for renters and more for households with children than for other households. However, while earlier research has found that owner-occupiers and households with children are especially sensitive to the neighbourhood ethnic composition (Ellen, 2000; Goyette et al., 2014; Greif, 2015; Xie and Zhou, 2012), I find that it is not the neighbourhood ethnic composition, but neighbourhood safety that is especially important for these groups. There are thus differences between ethnic groups, tenure groups and household types in the determinants of residential satisfaction. These differences might lead to selective mobility, segregation and high turnover rates. Policymakers in many countries try to create stable, attractive and mixed neighbourhoods (Bolt et al., 2010; Baum et al., 2009; Cheshire, 2007), also by attracting higher income households to deprived urban restructuring neighbourhoods (see Chapter 5). These insights in which neighbourhood characteristics are important to whom, are very important for effective policy design (Baum et al., 2009; Ellen et al., 2013; Pinkster et al., 2015). Ethnic differences in realising desires to leave the neighbourhood Residential dissatisfaction leads to mobility desires which could lead to residential mobility (Brown and Moore, 1970; Wolpert, 1965). Whether people realise their desire to move depends on their personal resources and restrictions (Mulder and Hooimeijer, 1999), there are thus individual differences in how successful people are in realising their desires to move. In Chapter 3, I focus on people who expressed a desire to leave their neighbourhood and study who realises this desire within two years and who manages to escape from poverty neighbourhoods or minority concentration neighbourhoods. To do this, I use a unique combination of survey data and register data. Cross-sectional survey data in which people are asked about their desire to leave the neighbourhood are merged with longitudinal register data on their subsequent residential mobility behaviour. This allows me to test if people with a desire to leave the neighbourhood actually do leave their neighbourhood within two years and which neighbourhoods they move to and from. Earlier research has found that ethnic minorities are less likely to leave ethnic minority concentration neighbourhoods (Bolt and Van Kempen, 2010; Pais et al., 2009; South and Crowder, 1998) and poverty neighbourhoods (Bolt and Van Kempen, 2003; Quillian, 2003; South et al., 2005; South and Crowder, 1997). It was, however, unclear whether this was explained by the fact that ethnic minorities less often want to leave these neighbourhoods, or whether they are less successful in leaving these neighbourhoods, also if they have a desire to leave. It is important to understand why there are ethnic differences in mobility patterns. If there are ethnic differences in mobility desires, this might lead to voluntary segregation. However, if certain (ethnic) groups are equally likely to want to leave certain neighbourhoods, but less successful than others in realising this desire, this indicates segregation is involuntary. I find that non-western ethnic minorities are less successful than natives in realising desires to leave their neighbourhood. In addition, they are found to be less likely than natives to escape from ethnic minority concentration neighbourhoods and poverty neighbourhoods, also if they have expressed a desire to leave their neighbourhood. Non-western ethnic minorities who realise a desire to leave their poverty or minority concentration neighbourhood, more often than natives, move to another poverty or minority concentration neighbourhood. In this chapter, I thus find ethnic selectivity in the realisation of mobility desires. These differences can lead to selective residential mobility and (involuntary) segregation. Neighbourhood selection of non-western ethnic minorities. Testing the own-group effects hypothesis using a conditional logit model Residential dissatisfaction will lead to a desire to move and people who realise their desire to move will select a new neighbourhood. Also in the selection of a destination neighbourhood there are differences between population groups. Neighbourhoods differ in population composition, amenities, dwelling availability and housing costs and population groups differ in resources, restrictions and preferences (Mulder and Hooimeijer, 1999), in their access to knowledge and opinions about neighbourhoods (Hedman, 2013) and in information about housing opportunities available to them (Bolt, 2001; Huff, 1986). In neighbourhood selection research, until now most studies characterise the neighbourhood based on a limited number of characteristics; they model the effect of personal characteristics on the probability to move to a poverty neighbourhood (Bolt and Van Kempen, 2003; Clark et al., 2006; Logan and Alba, 1993) or a minority concentration neighbourhood (Bråmå, 2006; Clark and Ledwith, 2007; Doff, 2010b; South and Crowder, 1998). However, in reality the selection of a neighbourhood will depend on multiple neighbourhood characteristics that are assessed simultaneously and in combination (Hedman et al., 2011). Ethnic minorities have been found to be more likely than natives to move to minority concentration neighbourhoods (Clark and Ledwith, 2007; Doff, 2010b; South and Crowder, 1998). However, this is not necessarily explained by the ethnic composition, also other neighbourhood characteristics correlated with ethnic composition might explain why especially ethnic minorities move to ethnic minority concentration neighbourhoods. In Chapter 4, I estimate the effect of various neighbourhood characteristics on neighbourhood selection of ethnic minority households. I use a conditional logit model, which allows me to simultaneously take into account multiple neighbourhood characteristics and thereby to distinguish the effect of the share of the own ethnic group, other ethnic minority groups and housing market characteristics on neighbourhood selection. Ethnic minorities are found to more often than others move to neighbourhoods with low dwelling values and high shares of social housing. These areas are often also ethnic minority concentration neighbourhoods, thus, housing market characteristics partly explain why ethnic minorities more often than others move to ethnic minority concentration neighbourhoods. Also when housing market characteristics are taken into account, I find evidence for own group effects; ethnic minorities are more likely to move to neighbourhoods with higher shares of their own ethnic group. Most likely, ethnic minorities select these neighbourhoods because they prefer to live among family or other own group members, and/or because they find a dwelling via their mono-ethnic network. This chapter focuses specifically on the four largest ethnic minority groups in the Netherlands. I find that for Surinamese and Antilleans the combination of housing market characteristics and own group effects explains why they more often than natives move to ethnic minority concentration neighbourhoods. Turks and Moroccans, however, are found to move more often to concentration neighbourhoods of ethnic minorities (other than their own ethnic group), also when housing market characteristics and own group effects are taken into account. Discrimination or fear of discrimination most likely explains why Turks and Moroccans are not willing or able to move to native majority concentration neighbourhoods. Mixed neighbourhoods; effects of urban restructuring and new housing development Many European countries use mixed housing policies to decrease the spatial concentration of low-income households. Within the Netherlands, large scale urban restructuring programs have been implemented in which inexpensive social rented dwellings in deprived neighbourhoods are demolished and replaced by more expensive and more often owner-occupied dwellings (Kleinhans, 2004). These urban restructuring programs have attempted to attract middle- and higher income households to deprived neighbourhoods. However, at the same time large numbers of expensive and mostly owner-occupied dwellings have been built on greenfield locations around the major cities. Urban restructuring programs might be less successful in attracting higher income households to deprived neighbourhoods when they have to compete with large scale greenfield development. In addition, greenfield development creates opportunities for relatively high income households to leave existing neighbourhoods, which will accelerate the process of selective outflow and income sorting and thereby increase the spatial concentration of low income households who are left behind. In Chapter 5 I study the effect of urban restructuring and new housing development on selective mobility patterns and income segregation. I compare three urban regions in the Netherlands with different patterns of urban restructuring and greenfield development. I use longitudinal register data to study income and income development of people who move to or from various neighbourhood types or to newly built dwellings and the effects of these selective mobility patterns on income segregation. I find that urban restructuring programs within deprived neighbourhoods are successful in attracting middle and higher income households, also when they have to compete with large scale greenfield development within the same urban region. Large scale greenfield development, however, leads to an outflow of relatively high income households from existing neighbourhoods. This outflow of higher income households leads to a further concentration of low income households in deprived neighbourhoods and an overall increase in residential income segregation. Residential segregation and interethnic contact in the Netherlands In Chapters 2 to 5 I study selective residential mobility and neighbourhood choice, while in Chapter 6 I study presumed neighbourhood effects mechanisms. According to the neighbourhood effects literature, one of the mechanisms through which neighbourhood effects transpire is via social interactions with neighbours (Ellen and Turner, 1997; Erbring and Young, 1979; Galster, 2012). Social interactions with natives provide ethnic minorities with the opportunity to learn the majority language, standards and values (Lazear, 1999), and with access to valuable information not present within the own ethnic network. Living in ethnic minority concentration neighbourhoods might reduce the opportunities for ethnic minorities to interact with natives and thereby hamper their integration and there life chances. Policymakers in many European countries therefore perceive concentrations of ethnic minorities as undesirable and try to create more mixed neighbourhoods (Bolt, 2009). It is, however, unclear to what extent the population composition of the residential neighbourhood determines social interactions, as people are found to increasingly have social contacts over larger areas (Boomkens, 2006). Therefore, in Chapter 6 I test whether the ethnic composition of the residential neighbourhood affects interethnic contact. I estimate a multilevel binary logistic regression model explaining whether or not ethnic minorities have contact with native Dutch people. This regression model includes both personal characteristics and neighbourhood characteristics including the share of native Dutch people in the neighbourhood. In earlier research (Gijsberts and Dagevos, 2005; Van der Laan Bouma-Doff, 2007) ethnic minorities have been found to have less contact with natives if the share of natives in the neighbourhood is lower, however, I find no effect of the neighbourhood ethnic composition on interethnic contact. Whether ethnic minorities have contact with the native majority is mainly explained by their individual characteristics such as educational level and household type. Also differences are found between ethnic minorities who live in the four largest cities -cities with high shares of ethnic minorities- and ethnic minorities in other cities with much lower shares of ethnic minorities. When these personal and regional characteristics are taken into account, the ethnic composition of the neighbourhood does no longer affect whether ethnic minorities have contact with the native majority. It is therefore unlikely that living in minority concentration neighbourhoods hampers life chances and integration of minorities via social interactive mechanisms. Ethnic residential segregation on neighbourhood level does not affect ethnic minorities’ social contact with the native majority and thus does not necessarily hamper integration and life chances of ethnic minorities. Conclusions: Selective mobility, segregation and neighbourhood effects The aim of this thesis is to gain more insight in both the causes and the consequences of segregation, through studying both individual residential mobility and neighbourhood selection and neighbourhood effects. Various authors have argued that selection bias is one of the main challenges in neighbourhood effects research (Harding, 2003; Sampson et al., 2002; Van Ham and Manley, 2012). It is not possible to completely eliminate selection bias from neighbourhood effects research, however, insight in selection will help to address selection bias (Manley and Van Ham, 2012; Van Ham and Manley, 2012; Winship and Mare, 1992). This thesis provides insight in both neighbourhood selection and neighbourhood effects and creates a link between these two fields of literature. It adds to the previous research as it studies selectivity in various aspects of the residential mobility process, thereby providing a more thorough insight in the causes of selective residential mobility and segregation. A central finding of this thesis is that there is non-random selection of people into neighbourhoods. Individual characteristics such as ethnicity, tenure, household type and income affect residential satisfaction, mobility preferences and behaviour and neighbourhood selection. Because of this non-random selection into neighbourhoods, a correlation found between neighbourhood characteristics and individual outcomes does not prove the existence of a neighbourhood effect. In this thesis I distinguish separate ethnic minority groups which allows me to decompose the causes of ethnic selective mobility. Both ethnic minorities and natives are less satisfied in neighbourhoods with higher shares of (other) ethnic minorities, however, ethnic minorities are more satisfied if the share of their own ethnic group in the neighbourhood is higher. Ethnic minorities thus prefer to live among their own ethnic group or close to ethnic specific facilities and these own group effects are found to partly explain why ethnic minorities more often than natives move to minority concentration neighbourhoods. However, not only preferences but also constraints due to housing market characteristics or discrimination cause ethnic minorities to move to ethnic minority concentration neighbourhoods. In addition, ethnic minorities are found to be less successful in realising their desires to leave their neighbourhood. Ethnic residential segregation is thus partly voluntary and partly involuntary. Besides ethnic selectivity, I also found selectivity in the residential mobility process with regard to household type, tenure and income. Residential mobility is selective with regard to income because higher income households are more successful than lower income households in realising residential preferences, not necessarily because their preferences are different. Household type and tenure are found to affect both residential preferences and the ability to realise these preferences. Neighbourhood effects can transpire via a number of presumed mechanisms. To provide a better insight in neighbourhood effects, it is important to study these mechanisms. (Andersson and Musterd, 2010). Social interactive mechanisms assume that neighbourhood effects transpire because the population composition of the residential neighbourhood affects with whom you interact (Ellen and Turner, 1997; Galster, 2012). However, this thesis shows that the ethnic composition of the residential neighbourhood does not affect whether ethnic minorities have contact with the native majority population. It is therefore unlikely that living in minority concentration neighbourhoods hampers life chances and integration of minorities via social interactive mechanisms. Directions for further research In further research, firstly, it is important to gain a better understanding of the potential mechanisms through which neighbourhood effects transpire. Social interactive mechanisms assume that (neighbourhood effects transpire because) the residential neighbourhood affects your social network and social contacts. In this thesis, I found that ethnic segregation on the scale of the residential neighbourhood does not affect whether working age ethnic minorities have social contacts with natives. It is therefore unlikely that, for this group and on this scale, neighbourhood effects transpire via social interactive mechanisms. More research on segregation on different spatial scales and on different population groups could give insight in when, where and for whom neighbourhoods affect social interactions and thus under which circumstances neighbourhood effects can possibly transpire via social interactive mechanisms. Besides social interactive mechanisms, neighbourhoods are also expected to transpire via job access, stigmatisation, the quality of local services and institutions and environmental mechanisms. Also for these mechanisms it is important to derive clear hypotheses about how the neighbourhood affects its residents and to subsequently test these hypotheses. Further research could for instance test if people in neighbourhoods with lower accessibility of jobs are more often unemployed, or if employers prefer employees from ‘good’ neighbourhoods over equally qualified ones from stigmatised neighbourhoods. Different neighbourhood effects mechanisms will work on different neighbourhood scales, be important for different groups of people, after different times of exposure to different neighbourhood conditions. Research that explicitly tests whether, for whom and under which circumstance these presumed mechanisms are at work, can provide insight in how, when, where and for whom the residential neighbourhood can possiblyaffect its residents. Secondly, neighbourhood effects research would benefit from more research actually trying to understand neighbourhood selection. We need to both empirically and theoretically link neighbourhood selection research to neighbourhood effects research. Empirically, selection research can be linked to neighbourhood effects research by incorporating models of selection into neighbourhood effects studies. Although models incorporating selection will not be able to completely eliminate selection bias from neighbourhood effects research, such research can show how incorporating selection affects the outcomes of neighbourhood effects models and thus give insight in the effects of selection bias. Theoretically, it is important to understand selective residential mobility and neighbourhood choice and to create a theory of selection bias. A theory of selection bias should explain how and why which factors affect both neighbourhood selection and individual outcomes (Van Ham and Manley, 2012). Such a theory could be used to design quasi-experimental studies, to invent new controls for selection bias, or to argue to what extent outcomes from neighbourhood effects studies are biased. This thesis provided some first ideas of what should be included in a theory of selection bias, but more research is needed. Differences in opportunities, differences in residential preferences and differences in access to information lead to individual differences in residential mobility decisions and outcomes and thus to selection bias. More insight is needed in why preferences and opportunities are different and in individual search strategies and decision-making processes; why do some individuals accept a certain dwelling in a certain neighbourhood while others continue searching for better housing opportunities? Policy implications This thesis finds that segregation is partly voluntary, caused be preferences to live among similar people and partly involuntary, caused by group differences in constraints induced by housing market characteristics or discrimination. To the extent that segregation is voluntary it will be neither possible nor useful to create stable mixed neighbourhoods (Cheshire, 2007). However, involuntary segregation can be, and has to be, addressed by policy-makers. Policies that reduce constraints and increase the options for households to move to a neighbourhood of their preference can reduce involuntary segregation and increase residential satisfaction. These policies, however, do not necessarily lead to more mixed neighbourhoods as people might use their increased freedom of neighbourhood choice to move close to similar people. Social interactions between people of various ethnic and socio-economic groups are important for emancipation and integration and to prevent segregated and separated worlds that can lead to fear and exclusion. However, as the population composition of the neighbourhood does not necessarily determine with whom people interact, creating mixed neighbourhoods is necessary nor sufficient to promote social integration. Other policy efforts that promote social contacts between various ethnic and socio-economic groups remain necessary. This thesis finds no neighbourhood effect of the ethnic composition of the residential neighbourhood on whether working age ethnic minorities in the Netherlands have contact with native Dutch people. However, working age people leave their small residential area on a daily basis and within the Netherlands, most high ethnic minority concentration neighbourhoods contain relatively high shares of natives. This level of segregation, on this spatial scale, is found to have no neighbourhood effect on contact. If, however, larger areas would become concentrations of very high shares of deprived households or ethnic minorities, residents will no longer have opportunities to meet and interact with more resourceful people or with the native majority. Therefore, continuing policy attention is needed to prevent high levels of segregation at larger spatial scales.